PERAN PERBANKAN SYARIAH DI TENGAH PEREKONOMIAN UMAT - Hendro Lisa (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
This paper provides an overview of Islamic banking and its role amidstthe Muslims economics. Sharia Banking is a banking system developed by expending and engaging the Islamic principles. This term is popularly known as the Islamic Bank. Islamic economic is an original economic system, which directly comes from the values ​​of Islamic teachings. It is built on the true belief that the world’s nature and all of its contents are created by Allah SWT, so that as creatures and khalifatul fil ardh, humans are obliged to carry out two main tasks, namely believing in Allah and prospering the world according to His prescribed ways.